Jak kształtować kulturę zaufania i odpowiedzialności w szkole w warunkach promowania rywalizacji przez neoliberalizm? - Rutkowiak, Joanna (Wydawnictwo Naukowe UAM, 2012)
The text brings up the issue of forming the culture of trust at school as an element that is par-ticularly important for the principle of social capital. This subject is presented in a wider con-text and based on the assumption that not only does the quality of social life filter and is reflec-ted in the quality of the educational institution, but it also puts pressure on it.
How to form the culture of trust and responsibility at school when rivalry is promoted by neoliberalism?
Keywords: culture of trust; social capital; neoliberalism